2023
DOI: 10.2147/tcrm.s404799
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Prepectoral Breast Reconstruction

Abstract: Breast reconstruction can be divided into prepectoral breast reconstruction (PPBR) and subpectoral breast reconstruction (SPBR) according to the implant plane. The original prepectoral breast reconstruction was abandoned for a long time due to the frequent and severe complications. Now, advances in materials technology and improved methods of mastectomy have made safe prepectoral breast reconstruction possible. Moreover, a number of studies have gradually demonstrated the advantages of prepectoral breast recon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Over recent years, prepectoral reconstruction regained a new life, and it represents the first option in many breast units for selected patients. [40][41][42] The main limitation is the cost of ADMs, but the advantages are clear, and the results obtained using our new standardized technique provide excellent evidence to consider.…”
Section: Standard New Totalmentioning
confidence: 90%
“…Over recent years, prepectoral reconstruction regained a new life, and it represents the first option in many breast units for selected patients. [40][41][42] The main limitation is the cost of ADMs, but the advantages are clear, and the results obtained using our new standardized technique provide excellent evidence to consider.…”
Section: Standard New Totalmentioning
confidence: 90%
“…In the United Kingdom, fifty-five thousand women are diagnosed with breast cancer on an annual basis, and it has been found that 40% of these women require a mastectomy [ 1 ]. The removal of a breast can have a profound impact on the overall quality of life for these women, leading to psychological inferiority and a decrease in social integration [ 1 , 2 ]. As part of the comprehensive treatment for breast cancer, breast reconstruction plays a pivotal role as it not only enhances the aesthetic appearance but also restores the natural contours of the breast [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The predominant approach utilized in the United Kingdom for immediate reconstructions after mastectomy is an implant-based reconstruction (IBBR), accounting for nearly 70% of all cases [ 4 ]. When it comes to the placement of the implant, there are two categories to consider: prepectoral breast reconstruction (PPBR) and subpectoral breast reconstruction (SPBR) [ 2 ]. Prepectoral breast reconstruction was initially introduced in the early 1960s and showed great promise in its early results [ 5 ].…”
Section: Introductionmentioning
confidence: 99%